2011
DOI: 10.5194/tc-5-13-2011
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of pingos in northern Asia

Abstract: Abstract. Pingos are prominent periglacial landforms in vast regions of the Arctic and Subarctic. They are indicators of modern and past conditions of permafrost, surface geology, hydrology and climate. A first version of a detailed spatial geodatabase of 6059 pingo locations in a 3.5 × 10 6 km 2 region of northern Asia was assembled from topographic maps. A first order analysis was carried out with respect to permafrost, landscape characteristics, surface geology, hydrology, climate, and elevation datasets us… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 62 publications
0
28
0
4
Order By: Relevance
“…The distribution of pingos in relation to surface geology compares well with the analysis of pingos in northern Asia. Grosse and Jones (2011) found that 68% of the pingos were located in areas underlain by sandy to silty sandy substrates, whereby 12% were associated with alluvial and floodplain deposits. Mackay (1998) also discussed the preferential formation of pingos in areas underlain by thick sandy sediments, which had been subsequently overlain by a layer of finer material deposited during the active lake stage.…”
Section: Tablementioning
confidence: 98%
See 3 more Smart Citations
“…The distribution of pingos in relation to surface geology compares well with the analysis of pingos in northern Asia. Grosse and Jones (2011) found that 68% of the pingos were located in areas underlain by sandy to silty sandy substrates, whereby 12% were associated with alluvial and floodplain deposits. Mackay (1998) also discussed the preferential formation of pingos in areas underlain by thick sandy sediments, which had been subsequently overlain by a layer of finer material deposited during the active lake stage.…”
Section: Tablementioning
confidence: 98%
“…This estimate included roughly 1450 located along the western Arctic Coast of Canada (Stager, 1956;MacKay, 1979), 1500 in Alaska (Holmes et al, 1968;Carter and Galloway, 1979;Hamilton and Obi, 1982;Walker et al, 1985;Ferrians, 1988), with the remainder scattered in other regions of Canada (Pissart, 1967;Gurney and Worsley, 1997), Russia (Shumskii and Vtyurin, 1966;Vtyurin, 1975), Spitsbergen (Yoshikawa and Harada, 1995), Greenland (Müller, 1959;Worsley and Gurney, 1996), Svalbard (Yoshikawa and Harada, 1995), Scandinavia (Lagerbäck and Rohde, 1985), China (Wang and French, 1995), and Mongolia (Lomborinchen, 2000). However, a recent analysis of topographic map data covering 3.5 × 10 6 km 2 region of northern Asia has identified more than 6000 pingos (Grosse and Jones, 2011) and an updated Alaska pingo distribution and number map notes more than 3000 (Jorgenson et al, 2008). Thus, in reality there are likely more than 11,000 known pingos in the northern Hemisphere (Grosse and Jones, 2011).…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Pingo inventories were furthermore used in paleo‐environmental reconstructions in the Mackenzie Delta in Canada, on Seward Peninsula in Alaska and in Central Yakutia . A modern spatial database shows more than 6000 pingos in a 3.5 × 10 6 km 2 region in the Eurasian Subarctic and Arctic, and links the pingo distribution to permafrost and landscape characteristics, to surface geology and morphology, and to hydrology and climate …”
Section: Introductionmentioning
confidence: 99%